The Effect of Liquid Organic Fertilizer Substitution On The Growth And Production Of Caisim Using Hydroponic Wick System - Raden Sonny Soerojo Junior Junior; Kiki Rizky Apriani; Denih Wahyudin; Ruslan (JURNAL AGRIMENT, 2026)
Caisim is one of the vegetable crops whose consumption continues to increase along with population growth, especially in urban areas such as West Java. The fulfillment of vegetable demand in urban areas still heavily depends on agricultural production from rural regions. This condition is caused by land conversion in urban areas, which results in decreasing agricultural land availability. Therefore, cultivation methods that can overcome limited land availability are needed, one of which is the hydroponic system, which is currently developing rapidly within the community. However, hydroponic systems are still constrained by relatively high production costs, making substitution with Liquid Organic Fertilizer (LOF) necessary. This study aimed to determine the best LOF substitution. The study used a Completely Randomized Design (CRD) with one factor consisting of four treatments (100% AB mix, 70% AB mix + 30% LOF, 50% AB mix + 50% LOF, and 100% LOF), each with three replications, resulting in 12 experimental units. The results showed that the LOF substitution treatment that was not significantly different from the AB mix control was the 30% LOF treatment for all observation variables. However, no LOF substitution treatment was found to be significantly better than the AB mix control.